2015
DOI: 10.1080/15389588.2015.1101078
|View full text |Cite
|
Sign up to set email alerts
|

“Are you still driving?” Metasynthesis of patient preferences for communication with health care providers

Abstract: Aim To synthesize published qualitative studies to identify older adults’ preferences for communication about driving with healthcare providers. Background Healthcare providers play a key role in addressing driving safety and driving retirement with older adults, but conversations about driving can be difficult. Guides exist for family members and providers, but to date less is known about the types of communication and messages older drivers want from their healthcare providers. Design Qualitative metasyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Older drivers who anticipate and prepare for driving cessation experience better health outcomes, emphasizing the benefits of advance planning. 3 Yet few participants had discussed driving safety with family or physicians, which is consistent with past research and may reflect avoidance of this sensitive subject 13 or unawareness that many older adults are unable to drive for the last years of life. 2 Physicians in particular may believe that conversations about driving safety adversely affects patient-physician relationships, especially when they include recommendations for driving cessation.…”
Section: Discussionsupporting
confidence: 65%
“…Older drivers who anticipate and prepare for driving cessation experience better health outcomes, emphasizing the benefits of advance planning. 3 Yet few participants had discussed driving safety with family or physicians, which is consistent with past research and may reflect avoidance of this sensitive subject 13 or unawareness that many older adults are unable to drive for the last years of life. 2 Physicians in particular may believe that conversations about driving safety adversely affects patient-physician relationships, especially when they include recommendations for driving cessation.…”
Section: Discussionsupporting
confidence: 65%
“…Older people may be defensive and feel misjudged and scrutinized if family members or friends comment on their driving skills (Betz et al, 2015;Liddle et al, 2016). We have found this to be the case, particularly when family members know of our research focus on older drivers.…”
Section: What Do Older Drivers Want From Family Members?mentioning
confidence: 85%
“…The issue of driving and driving cessation is an extremely challenging aspect of aging for many older people, their families, and their health teams (Betz, Scott, Jones, & DiGuiseppi, 2015;Liddle et al, 2016;Organisation for Economic Cooperation and Development, 2001). Road crash statistics indicate a complex situation where changing driving abilities, combined with increasing physical frailty, and vehicles and a built environment which are not optimized for older people, lead to an increasing road toll (Cicchino, 2015;Koppel, Bohensky, Langford, & Taranto, 2011).…”
mentioning
confidence: 99%
“…Other research has shown that older adult drivers support routine questioning of driving habits by health professionals as a way to normalize the topic of driving cessation (Betz et al 2013), but that this communication should occur over time rather than abruptly (Betz et al 2016). Vision-care providers seem to display more confidence in their abilities to determine whether an older adult can still drive safely.…”
Section: Discussionmentioning
confidence: 99%